Electrochemical technologies for energy storage and conversion : [Volume 1 & 2] - Liu, Ru-Shi.; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
In this handbook and ready reference, editors and authors from academia and industry share their in-depth knowledge of known and novel materials, devices and technologies with the reader. The result is a comprehensive overview of electrochemical energy and conversion methods, including batteries, fuel cells, supercapacitors, hydrogen generation and storage as well as solar energy conversion. Each chapter addresses electrochemical processes, materials, components, degradation mechanisms, device assembly and manufacturing, while also discussing the challenges and perspectives for each energy storage device.
Publisher website.
Keywords: Energy storage; Electrochemistry; Electrical engineering; Engineering; Electrochemistry; Energy storage; Electronic books